2021
DOI: 10.1002/ijc.33804
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell intrinsic Toll‐like receptor 4 signaling promotes melanoma progression and metastatic dissemination

Abstract: Most melanoma-associated deaths result from the early development of metastasis.Toll-like receptor 4 (TLR4) expression on nontumor cells is well known to contribute to tumor development and metastatic progression. The role of TLR4 expression on tumor cells however is less well understood. Here we describe TLR4 as a driver of tumor progression and metastatic spread of melanoma cells by employing a transplantable mouse melanoma model. HCmel12 melanoma cells lacking functional TLR4 showed increased sensitivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Cancer cell-derived long pentraxin 3 promoted melanoma migration through TLR4/NF-κB signalling pathway 35 . TLR4-knockout melanoma cells exhibited impaired migratory capacity and significantly reduced ability to metastasise to the lungs 36 . Suppressing TLR4 or targeting TLR4 in melanomas could inhibit proliferation, migration, and invasion of tumour cells 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cell-derived long pentraxin 3 promoted melanoma migration through TLR4/NF-κB signalling pathway 35 . TLR4-knockout melanoma cells exhibited impaired migratory capacity and significantly reduced ability to metastasise to the lungs 36 . Suppressing TLR4 or targeting TLR4 in melanomas could inhibit proliferation, migration, and invasion of tumour cells 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It is classified as an antineoplastic agent, protein kinase inhibitor, antineoplastic and immunomodulating agent, cytochrome P-450 CYP1A2 inhibitor, cytochrome P-450 CYP1A2 inducer, CYP2D6 inducer, CYP2D6 inducer (strong), and CYP3A4 inhibitor. To date, it has been shown that TLR4 and its signaling pathway promote migration of human melanoma cells [ 95 , 96 ], but no studies showing a direct effect of vemurafenib on TLR4 have been conducted yet.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggest that investigated functional polymorphisms, associated with structural changes of the TLR4 extracellular domain, could have important consequences on the TLR4 signaling that might affect melanoma progression. A recent study on in-vitro and in-vivo mouse models of melanoma by Rogava et al [24] identifies TLR4 as a driver of melanoma cells migration and metastasis. TLR4 promotes melanoma growth and metastatic progression in vivo but decreases the growth of TLR4 knockout melanoma cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 promotes melanoma growth and metastatic progression in vivo but decreases the growth of TLR4 knockout melanoma cells in vitro . A suggested mechanism for this apparently contradictory role of TLR4 on melanoma growth in vivo and in vitro lies in the induction of a mesenchymal-like, invasive, and migratory phenotype, but with reduced proliferation capacity [24]. TLR4 could have an important role in the formation of a premetastatic niche in vivo , by providing the interaction of cancer cells with the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation